Empowering the 4Cs-based English Speaking with Multi-voiced Classroom for IUP Students - Permatasari, Ni Putu Intan (Journal Corner of Education, Linguistics, and Literature, 2025)
The ability to communicate effectively in English is a critical skill for university students navigating increasingly globalized academic and professional contexts. Beyond linguistic accuracy, 21st-century learners are expected to master the 4Cs: Critical thinking, Communication, Collaboration, and Creativity. However, traditional English-speaking instruction often emphasizes rote learning and accuracy, neglecting these broader competencies. This study explores how a multi-voiced classroom approach can empower 4Cs-based English speaking among students in the International Undergraduate Program (IUP) at Undiknas University. Using a qualitative descriptive design, data were collected through in-depth interviews with six IUP students who experienced multi-voiced English-speaking activities, including debates, peer-led discussions, and storytelling tasks. Thematic analysis revealed five key outcomes: enhanced confidence and reduced speaking anxiety, strengthened critical thinking skills, improved collaboration, greater creativity in spoken expression, and increased intercultural awareness. The findings suggest that the multi-voiced classroom fosters a psychologically safe environment that encourages active participation, supports co-construction of meaning, and promotes holistic communicative competence. This integrative approach aligns with global educational goals to produce graduates who are not only proficient in English but also adaptive, critical, collaborative, and creative thinkers. The study offers practical insights for language educators aiming to design more inclusive and competency-based speaking curricula in higher education.